The L.M. Montgomery reader. - Lefebvre, Benjamin (University of Toronto Press, 2014)
Following on the heels of the first volume of The L.M. Montgomery Reader, this second volume narrates the development of L.M. Montgomery's (1874-1942) critical reputation in the seventy years since her death.